Testing hypotheses for the functions of APC family proteins using null and truncation alleles in Drosophila. - McCartney, B.M.; Price, M.H.; Webb, R.L.; Hayden, M.A.; Holot, L.M.; Zhou, M.; Bejsovec, A.; Peifer, M. (Development, 2006)
Adenomatous polyposis coli (APC) is mutated in colon cancers. During normal development, APC proteins are essential negative regulators of Wnt signaling and have cytoskeletal functions. Many functions have been proposed for APC proteins, but these have often rested on dominant-negative or partial loss-of-function approaches. Thus, despite intense interest in APC, significant questions remain about its full range of cellular functions and about how mutations in the gene affect these. We isolated six new alleles of Drosophila APC2. Two resemble the truncation alleles found in human tumors and one is a protein null. We generated ovaries and embryos null for both APC2 and APC1, and assessed the consequences of total loss of APC function, allowing us to test several previous hypotheses. Surprisingly, although complete loss of APC1 and APC2 resulted in strong activation of Wingless signaling, it did not substantially alter cell viability, cadherin-based adhesion, spindle morphology, orientation or selection of division plane, as predicted from previous studies. We also tested the hypothesis that truncated APC proteins found in tumors are dominant negative. Two mutant proteins have dominant effects on cytoskeletal regulation, affecting Wnt-independent nuclear retention in syncytial embryos. However, they do not have dominant-negative effects on Wnt signaling.